LITERATURE SURVEY OF FINANCIAL PERFORMANCE DASHBOARD CONCEPTS - Eka Kristi Silalahi; Tora Fahrudin; Asniar Asniar (LPPM STIE Muhammadiah Bandung, 2025)
Improving efficiency and productivity is the main goal that every company wants to achieve. One of the solutions that supports to achieve this goal is to use the dashboard. However, it is not enough only because of the need to create an effective and efficient dashboard for the Company. Of course, dashboards are designed to be able to present important data both visually and interactively, which makes it easier to analyze and make good and correct decisions. This research aims to design an effective and efficient dashboard design for the Company. The methods used in this study are through literature study, user needs analysis, and prototype testing. The result of this research is a dashboard design that is integrated with the Company's information system, able to display data visualization. and able to display key performance metrics. With this dashboard, it is hoped that it can help the Company to monitor sales performance, identify the Company's finances, identify problems properly, and take the needed solutions.